ANALISIS FUNDAMENTAL SAHAM SYARIAH DAN SAHAM KOVENSIONAL TERHADAP KEBIJAKAN PEMBAYARAN DIVIDEN (Studi pada Perusahaan Manufaktur yang Terdaftar di JII dan LQ45 Periode 2010-2013) - Samira Hanim (Jurnal Administrasi Bisnis, 2015)
This study is to determine the simultaneous and partial effect of Cash Ratio, Current Ratio (CR), Total Assets Turnover (TATO), Return On Equity (ROE), Earning Per Share (EPS), and Debt Equity Ratio (DER) to the Dividend Payout Ratio (DPR). This research is an explanatory research with a quantitative approach. The samples used in this study were 8 manufacturing companies, including six companies listed in Jakarta Islamic Index (JII) and two companies listed in LQ45. The data analysis used in this study is a multiple linear regression analysis. The results of this study are Cash Ratio, Current Ratio (CR), Total Assets Turnover (TATO), Return On Equity (ROE), Earning Per Share (EPS), and Debt Equity Ratio (DER) simultaneous affecting the Dividend Payout Ratio (DPR) on manufacturing companies listed in JII and LQ45. These results demonstrated by the probability value of F 0,000 (α ≤ 0.05) on companies listed in JII and 0,029 (α ≤ 0.05) on companies listed in LQ45. Cash Ratio, Current Ratio (CR), Total Assets Turnover (TATO), and Debt Equity Ratio (DER) are partially affecting the Dividend Payout Ratio (DPR) on the company listed in JII, while Current Ratio (CR) and Earning Per Share (EPS) are partially affecting significant to dividend Payout Ratio (DPR) on the companies listed in LQ45. The obtained results are proved by the results of the t test of each independent variables on the dependent variable and the result of the Sig. ≤ α (α = 0.05) that indicates the variables have significant effect partially. Keywords: Cash Ratio, Current Ratio, Total Assets Turnover, Return On Equity, Earning Per Share, Debt Equity Ratio, Dividend Payout Ratio Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh secara simultan dan parsial variabel Cash Ratio, Current Ratio (CR), Total Assets Turnover (TATO), Return On Equity (ROE), Earning Per Share (EPS), dan Debt Equity Ratio (DER) terhadap Dividend Payout Ratio (DPR). Jenis penelitian ini adalah penelitian penjelasan (explanatory) dengan pendekatan kuantitatif. Sampel yang digunakan dalam penelitian ini sebanyak 8 perusahaan manufaktur, diantaranya 6 perusahaan yang tergabung dalam JII dan 2 perusahaan yang tergabung dalam LQ45. Analisis data yang digunakan dalam penelitian ini adalah analisis regresi linier berganda. Hasil dari penelitian ini yaitu Cash Ratio, Current Ratio (CR), Total Assets Turnover (TATO), Return On Equity (ROE), Earning Per Share (EPS), dan Debt to Equity Ratio (DER) berpengaruh secara simultan terhadap Dividend Payout Ratio (DPR) pada perusahaan manufaktur di JII dan LQ45. Hasil tersebut dibuktikan dengan nilai probabilitas Fhitung 0,000 (α ≤ 0,05) pada perusahaan yang tergabung dalam JII dan 0,029 (α ≤ 0,05) pada perusahaan yang tergabung dalam LQ45. Cash Ratio, Current Ratio (CR), Total Assets Turnover (TATO), dan Debt to Equity Ratio (DER) berpengaruh secara parsial terhadap Dividend Payout Ratio (DPR) pada perusahaan di JII, sedangkan pada perusahaan di LQ45 yang berpengaruh signifikan secara parsial terhadap Dividend Payout Ratio (DPR) adalah Current Ratio (CR) dan Earning Per Share (EPS). Hasil tersebut dibuktikan dari hasil uji t masing-masing variabel independen terhadap variabel dependen, dan hasil yang diperoleh yaitu variabel yang berpengaruh signifikan secara parsial memiliki nilai Sig. ≤ α (α = 0,05). Kata kunci: Cash Ratio, Current Ratio, Total Assets Turnover, Return On Equity, Earning Per Share, Debt Equity Ratio, Dividend Payout Ratio